2010
DOI: 10.1111/j.1551-2916.2010.04255.x
|View full text |Cite
|
Sign up to set email alerts
|

Judd-Ofelt Spectroscopic Study of Er:In:LiNbO3 Crystals For Integrated Optics

Abstract: Er:In:LiNbO3 crystals were grown by Czochralski method from congruent melts containing 0.5/0.5, 0.5/1.0, and 0.5/1.5 mol%/mol% Er2O3/In2O3. The Er and In concentrations in the crystals were determined by neutron activation analysis. The refractive indices at the 473, 633, and 1536 nm wavelengths were measured by prism coupling technique. The unpolarized Er3+ and OH− absorption spectra of the crystals were measured at room temperature. The Er3+ absorption cross‐section spectra were determined, and the Er3+ spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…The absorption decrease is obviously because the MgO doping reduces the intrinsic defects in the crystal and hence the absorption of the 3480 cm À1 component. Similar doping effects on the OH À absorption were also observed for the other dopants such as transition metal ions Zn 2þ [18] and In 3þ [20], which are also antiphotorefractive dopants and have an optical damage threshold concentration of 7.5 and 3.0 mol%, respectively, for a crystal grown from a congruent melt. On the other hand, doping with some other transition metal ions such as Fe 3þ [19,21] and Ti 4þ [22] strengthens the photorefractive effect (This is also the case for the rare-earth Er 3þ dopant [2]).…”
Section: Mgo-codoping Effectssupporting
confidence: 66%
See 1 more Smart Citation
“…The absorption decrease is obviously because the MgO doping reduces the intrinsic defects in the crystal and hence the absorption of the 3480 cm À1 component. Similar doping effects on the OH À absorption were also observed for the other dopants such as transition metal ions Zn 2þ [18] and In 3þ [20], which are also antiphotorefractive dopants and have an optical damage threshold concentration of 7.5 and 3.0 mol%, respectively, for a crystal grown from a congruent melt. On the other hand, doping with some other transition metal ions such as Fe 3þ [19,21] and Ti 4þ [22] strengthens the photorefractive effect (This is also the case for the rare-earth Er 3þ dopant [2]).…”
Section: Mgo-codoping Effectssupporting
confidence: 66%
“…As its vibration is sensitive to the change of surrounding ion environment, the OH À absorption can be used to study the defect structure of its host, its vibration frequency can serve as an identifier for judging an LN crystal being below or above the threshold concentration of photorefractive damage. Since the first study concerning with the infrared absorption of OH À stretching vibration in pure LN was reported by Smith et al in 1968 [6], the OH À absorption characteristics in pure [7e13] and various LN crystals singly doped with Mg [14e17], Zn [18], Fe [19], In [20] or doubly doped with Mg/ Fe [21] and Mg/Ti [22] have been extensively studied. In contrast, only a few papers with regard to the Mg/rare-earth-ion codoped LN crystals were reported previously [23e25] while a systematic relevant study on the rare-earth doped LN crystals could not be found in the previous literatures as far as we know.…”
Section: Introductionmentioning
confidence: 99%
“…14 The In and Er dopant concentrations in the crystals studied were determined by neutron activation analysis. 16 The results show that the Er concentration in crystal is 0.95 6 0.04, 0.93 6 0.04, and 0.92 6 0.04 mol% for the growth melts containing 0.5, 1.0, and 1.5 mol% In 2 O 3 , respectively. The In concentration in the crystal is 1.20 6 0.06, 1.91 6 0.09, and 2.60 6 0.10 mol%, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…10 Similar spectral features should be also true for the In 2 O 3 doping case. The OH absorption study 16 has shown that the OH vibration frequency of the two lightly In 2 O 3 -doped crystals peaks at ;3490 cm À1 and hence the two crystals are all below the photorefractive threshold. As the In 2 O 3 doping level is increased to 1.5 mol%, the OH vibration frequency peaks at 3510 cm À1 , suggesting that the 1.5 mol% In 2 O 3 -doped crystal is just above the photorefractive damage threshold concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation